2013
DOI: 10.3989/gya.130512
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Iberian pigs according to intensive feeding by chemsensor

Abstract: RESUMEN Clasificación de cerdos ibéricos en función de su alimentación mediante ChemSensorLa calidad de la carne de cerdo está muy relacionada con la alimentación que ha tenido en su fase de cebo, por lo que se están desarrollando métodos analíticos que determi nen la misma. Entre ellos se encuentra el ChemSensor o Sensor químico que incorpora análisis multivariante a la tec nología de cromatografía de gases con detector de masas. Esta técnica permite agrupar alimentos por similitudes y me diante un modelo mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Therefore, this finding could trigger a discussion about the possible categorization of this feeding strategy, in order to distinguish it from the exclusive feeding of natural resources and to clarify the market. In this sense, there are some authors who have suggested a modification of Iberian product categories in order to simplify the market [36]. This is consequence of the consumers' greater demand of complete information from the products, whose selection is nowadays frequently difficulted due to an ambiguous labelling or origin information.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this finding could trigger a discussion about the possible categorization of this feeding strategy, in order to distinguish it from the exclusive feeding of natural resources and to clarify the market. In this sense, there are some authors who have suggested a modification of Iberian product categories in order to simplify the market [36]. This is consequence of the consumers' greater demand of complete information from the products, whose selection is nowadays frequently difficulted due to an ambiguous labelling or origin information.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison used in the present study between AF and FF Iberian pigs has often been evaluated in the literature using other analytical techniques for preliminary evaluations and authentication purposes of the feeding regime of this breed [6,[33][34][35]. In fact, this simplification of the current categorisation to only two groups has even been suggested by some authors as an option to clarify the market [36], since the current labelling may be confusing for customers [37,38]. In this regard, the results here presented would contribute to cover society's increasing demand of valuable information about food authenticity and production systems [39], as the methodology used could support certification work in Iberian pig production and therefore in final products.…”
Section: Resultsmentioning
confidence: 99%